Application of the ICAN model for transition-aged youth with intellectual and developmental disabilities - Watts, MS, CTRS, Cassandra; Porter, PhD, CTRS, Heather R.; Snethen, PhD, CTRS, Gretchen (American Journal of Recreation Therapy, 2018)
Successful community integration (CI) is a concern for transition-aged youth (TAY) with intellectual and developmental disabilities (IDD). TAY with IDD transitioning into adulthood show a decrease in community participation as they age, participate less frequently in the community, have less environmental support, have low employment rates, and tend to participate in more isolated, solitary, and passive activities. In an attempt to improve CI outcomes for this population, transitioning services are mandated in the public-school system; however, lack of compliance and a consistent model pose major concerns. Although developed for adults with schizophrenia spectrum disorders, the Independence through Community Access and Navigation (ICAN) intervention may be a relevant CI model for recreational therapists (RTs) to use with TAY with IDD. It is a theoretically grounded intervention designed to support participation in community activities through coparticipation with an RT and skill building in the community environment. This article will present issues regarding CI for TAY with IDD, discuss the need for an RT transitioning model for this population, and present a rationale for the application of the ICAN model by RTs for TAY with IDD.